2006
DOI: 10.1007/bf02893428
|View full text |Cite
|
Sign up to set email alerts
|

p53 codon 72 polymorphism in basal cell carcinoma of the skin

Abstract: Basal cell carcinoma (BCC) is the most prevalent cancer in Iran. A common polymorphism at codon 72 of exon 4 of p53 tumor suppressor gene has been reported to be associated with increased inheritable susceptibility to several cancers. In the present study the frequency of p53 codon 72 polymorphism in 91 patients with BCC of skin, compared to 465 healthy normal individuals, was investigated. In total, there was no significant difference in the p53 genotypes between patients and controls. However, there was an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…A previous study which analyzed the correlation between the p.R72P polymorphism and p53 mutation in breast cancer patients, has reported that p53 mutation was more prevalent in the Arg/Arg genotype than those of the Pro/ Pro genotype (Langerod et al, 2002). The Arg allele at codon 72 of the TP53 has been suggested to affect the risk of UV-induced basal cell carcinoma (Pezeshki et al, 2006) as the frequency of the Arg allele was significantly higher in sun-exposed patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study which analyzed the correlation between the p.R72P polymorphism and p53 mutation in breast cancer patients, has reported that p53 mutation was more prevalent in the Arg/Arg genotype than those of the Pro/ Pro genotype (Langerod et al, 2002). The Arg allele at codon 72 of the TP53 has been suggested to affect the risk of UV-induced basal cell carcinoma (Pezeshki et al, 2006) as the frequency of the Arg allele was significantly higher in sun-exposed patients compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…Pezeshki et al (21) demonstrated that the frequency of the Arg allele was significantly higher in sun-exposed patients compared to controls, suggesting that Arg allele at codon 72 of the p53 gene might affect the risk of UV-induced basal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Genotyping of p53 codon 72. p53 codon 72 polymorphism detection was carried out by an allele specific PCR described by Pezeshki et al (31) with slight modification on a Palm Cycler (Corbett Research, Australia). To detect the p53 codon 72 polymorphism, two primer sets in separate tubes were used, one to amplify the Arg allele and the other to amplify the Pro allele as follows: Arg forward, TCC CCC TTg CCg TCC CAA, Arg reverse, CTg gTg Cag ggg CCA CgC; Pro forward, gCC AgA ggC TgC TCC CCC, Pro reverse, CgT gCA AgT CAC AgA CTT.…”
Section: Studymentioning
confidence: 99%
“…conducted to find these association since most of the studies tried to analyze the associations of the polymorphism in cancer patients and healthy population (31,34). Moreover, Arg/ Arg genotype was found dominant in both types of NMSC.…”
Section: B Amentioning
confidence: 99%